2010
DOI: 10.1148/radiol.10100495
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative MR Imaging of Brain Iron: A Postmortem Validation Study

Abstract: Because of their strong linear correlation with iron concentration, both R2 and R2* can be used to measure iron deposition in the brain. Because R2* is more sensitive than R2 to variations in brain iron concentration and can detect differences in white matter, it is the preferred parameter for the assessment of iron concentration in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
442
0
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 452 publications
(493 citation statements)
references
References 39 publications
41
442
0
10
Order By: Relevance
“…The location of iron accumulation was further associated with microstructural axonal damage. Recently, several studies reported a linear relationship between transverse magnetic resonance relaxation rates and iron content in healthy subjects and postmortem tissue, indicating that R2* imaging is a good surrogate for detecting cerebral iron accumulations 25, 26, 27. By a rater‐driven approach, T2*‐weighted imaging of SAH patients in their chronic stage allowed to identify signal alterations within the subarachnoid space even years after the onset 28, 29, 30.…”
Section: Discussionmentioning
confidence: 99%
“…The location of iron accumulation was further associated with microstructural axonal damage. Recently, several studies reported a linear relationship between transverse magnetic resonance relaxation rates and iron content in healthy subjects and postmortem tissue, indicating that R2* imaging is a good surrogate for detecting cerebral iron accumulations 25, 26, 27. By a rater‐driven approach, T2*‐weighted imaging of SAH patients in their chronic stage allowed to identify signal alterations within the subarachnoid space even years after the onset 28, 29, 30.…”
Section: Discussionmentioning
confidence: 99%
“…54 Proton magnetic resonance spectroscopy ( 1 H MRS) can add information on the biochemical nature of MS related abnormalities, by quantifying several CNS metabo lites. 55 T2 hypointense areas and reduced T2* relaxation time (or its reciprocal R2*) are thought to be associated with iron deposition, which is believed to be a sign of neurodegeneration in patients with MS. 56 Application of these techniques to characterize the extent and distribution of MS related damage within focal lesions or in normal appearing white and grey matter has shown that tissue disruption in patients with progressive disease is more severe and more widely distributed than in patients with relapsing forms of MS. 57 Additionally, struc tural CNS damage has been shown to progress at different rates across the major clinical pheno types of MS. Global and regional quantitative MRI abnormalities corre late with the severity of clinical and cognitive impairment, and advanced and quantitative MRI techniques seem to be useful for predicting subsequent accumulation of clinical disability and cognitive impairment.…”
Section: Focal Lesionsmentioning
confidence: 99%
“…In fact, several studies report a linear relationship between iron content and T 2 in brain tissue. [23][24][25] …”
Section: Endogenous T 2 Contrastmentioning
confidence: 99%
“…63 Most iron is chelated and stored in the protein ferritin as Fe 3+ , 23,63 which shortens water proton T 1 and T 2 relaxation times. 23,64 Accordingly, several studies reported T 1 and T 2 effects as a function of iron content 10,[23][24][25]65 in the human brain, with concentration in the globus pallidus (GP) among the highest. Though T 2 W MR imaging shows a similar pattern of signal reduction around the GP (white arrows in Fig.…”
Section: Nerve Cellsmentioning
confidence: 99%